"Devil's casino: friendship, betrayal and high-stakes games played inside Lehman brothers" - "Ward,Vicky" (New Delhi, 2010)
The inside story of what really happened at Lehman Brothers andwhy it failedIn The Devil's Casino: Friendship, Betrayal, and the High StakesGames Played Inside Lehman Brothers, investigative writer andVanity Fair contributing editor Vicky Ward takes readers insideLehman's highly charged offices. What Ward uncovers is a muchbigger story than Lehman losing at the risky game of collateralizeddebt obligations, swaps, and leverage.A can't put it down page turner that opens the world of WallStreet to view unlike any book since Bonfire of the Vanities,except that The Devil's Casino isn't fiction. * Details what went on behind-the-scenes the weekend LehmanBrothers failed, as well as inside Lehman during the twenty yearspreceding it * Describes the feudal culture that proved both Lehman's strengthand its Achilles' heel * Written by Vicky Ward, one of today's most connected businessand finance writersOn Wall Street, Lehman Brothers was cheekily known as "the catwith nine lives." But as The Devil's Casino documents, this catpushed its luck too far and died?the victim of men and womenblinded by arrogance.
Keywords: Lehman Brothers (1995-)-History